Analysis of oligonucleotides by hydrophilic interaction liquid chromatography coupled to negative ion electrospray ionization mass spectrometry. - Gong, L; McCullagh, J (2011)
Hydrophilic interaction liquid chromatography (HILIC) is here successfully coupled to negative-ion electrospray ionization time-of-flight mass spectrometry (ESI-TOFMS) for the analysis of synthetic and chemically modified oligonucleotides. Separation was performed on a 2.1 mm × 100 mm PEEK ZIC HILIC column packed with hydrophilic stationary phase with a permanent zwitterionic functional group and a particle size of 3.5 μm with an average pore diameter of 200Å. A method was developed to separate homogeneous and heterogeneous oligonucleotides as well as methylated oligonucleotides using a quaternary pumping system containing ammonium acetate and water with an acetonitrile gradient. Analyses of oligonucleotides were performed by LC/MS with a detection limit of 2.5 picomole (20 mer) with signal to noise ratio (S/N) of 4.12. The influence of the eluent composition, type of buffer and its concentration, and organic modifier were also evaluated. The HILIC LC/MS method presented in this paper used common, 'MS friendly', mobile phases achieving sensitive and selective oligonucleotide analysis.